Rise of eating disorders and obesity in young adults during the COVID-19 pandemic - Ali Malik, Ghulam Mustafa; Faheem, Samar; Muhammad, Faeez (Journal of the Pakistan Medical Association, 2022)
Dear Madam, COVID-19 has taken the world by storm, brought everything to an alarming halt and has put forward a plethora of challenges into the life of everyday people. These challenges include an outbreak of Eating Disorders (ED) during the pandemic, which inevitably leads to obesity; it was found that 41.7% of adolescents had gained more unhealthy weight; which would tether towards obesity during the period of COVID-19.1 The pandemic has brought many problems into the lives of the Pakistani population. Social isolation and stress from lockdown and uncertainties brought forth from COVID-19, and the restrictions enforced by the governmental bodies have been contributing factors in increasing the rising rate of eating pathologies amongst young adults.2 These disorders, if left untreated, will develop into a multitude of life-threatening diseases due to a sudden increase in body weight. In a study done in Pakistan, around 40% of the participants gained weight during COVID-19 lockdown, and 67% saw decreased physical activity.3 It is difficult to maintain healthy eating in low-income countries where access to unhealthy food in bulk is easier compared to healthy foods. Physical activities are almost non-existent in places without a culture of walking or exercising outdoors. In a study by Rodgers et al., it is stated that people’s food choices during COVID-19 are influenced by isolation, disrupted routines, a lack of physical activity, and emotional distress in their lives. The authors also state that social media plays a role, worsening young people’s relationship with food by calling for specific diets either because of diet culture or the fear of contamination. Media also covers stressful events that increase anxiety in individuals and contribute to eating disorders, such as binge eating disorder.4 These eating behaviours that affect people during a lockdown are predicted to have far-reaching effects in the future through indirect consequences of COVID-19. Unhealthy lifestyle habits could impair immunity and even decrease the effectiveness of vaccines.5 It is clear that the rise of eating disorders in young adults during the pandemic needs to be examined further. Underlying causes such as unavailability of healthy food, stress, and isolation should be addressed in further research. Advice regarding lifestyle modification should be tailored accordingly for lockdown: for example, home workouts replacing gyms, easy access to healthy food, and telemedicine that replaces in-clinic therapy for EDs.